Are OBE‐trained learners ready for university mathematics? - Johann Engelbrecht; Ansie Harding; Patrick Phiri (Pythagoras, 2010)
The 2009 intake of university students were the first to have received complete school education within the recently implemented Outcomes‐Based Education (OBE) system. A feature of the matriculation examination results of these students was the exceptionally high Grade 12 marks for Mathematics. This paper addresses the question of how the 2009‐ intake of students performed at university with respect to general performance, general attributes, mathematical attributes and content related attributes. It appears that these students are better prepared with respect to personal attributes such as confidence. However, in many instances they are weaker than their predecessors with respect to mathematical and content related attributes. Yet, there are positive indications that these students adapt and improve over a semester. We make some suggestions on how to make the transition from secondary to university mathematics somewhat smoother.